Demand Analysis And Willingness To Pay (Wtp) Estimation For Digital Dentistry Technology Among Students Of The Faculty Of Dentistry, Andalas University - Dora Amelia Yoma; Elfindri; Sri Maryati (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Development digital dentistry technology has bring change significant in system education and practice medical modern teeth. Use technology such as intraoral scanners, computer- aided design/computer-aided manufacturing (CAD/CAM), virtual articulators, and three-dimensional printing (3D printing) are assessed capable increase efficiency, accuracy, and quality learning clinical student medical teeth. However Thus, the implementation digital dentistry technology requires cost relative investment tall so that required analysis economy related demand and capacity pay users to facility said. Research This aim For analyze request student as well as estimate Willingness to Pay (WTP) for use digital dentistry technology for students Faculty Andalas University Dentistry. Research results show that perception benefits and efficiency own influence significant towards students' WTP to digital dentistry technology (p<0.05). Barriers costs also show influence significant to decision student in pay use digital dentistry facilities. Meanwhile that, variable knowledge and stages education show connection positive However No all of it significant in a way statistics. findings study show that student look at digital dentistry technology as investment capable education increase quality learning and readiness face development practice medical modern teeth.